Analisis Dampak Oil Spill Di Teluk Balikpapan Terhadap Kehidupan Masyarakat Dalam Perspektif Hukum Dan Lingkungan - Ahyadi, Muhammad Yaris; Syarifudin, Abimanyu Putra; Khairunnisa, Alesha Zahira; Ximenes, Joana Dacosta; Hamdi, Muhammad Hilal (Bumi Lestari; Vol 21 No 1 (2021)DO - 10.24843/blje.2021.v21.i01.p03, 2021)
One form of marine pollution is an oil spill that can come from the fault of tanker activity while operating.An example of the case is the incident of oil spill in Balikpapan Bay due to the leak of pertamina's oil pipeline in 2018, 5 thousand liters of oil spilled and polluted the sea with an area of more than 12 thousand hectares.Using normative juridical methods, researchers will conduct an analysis of the impact of the oil spill in Balikpapan Bay on the lives of the surrounding community based on legal and environmental perspectives.The purpose of the author by making this paper is to know how the process of tackling and impacting oil spills so far for the surrounding community based on the law and the environment, can also be an input for the government to be able to resolve the case of oil spill in balikpapan bay that has lasted about 3 years, so that the lives of local people can run smoothly as before the oil spill incident.